ECOLOGICAL AND SOCIAL FACTORS' IMPACT ON THE GLOBAL OIL MARKET (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
This article examines the impact of ecological and social factors on the global oil market. It analyzes the ecological and social factors influencing the development of the oil industry and oil markets, as well as their significance and role in the global economy. Ecological factors, such as climate change, the transition to green energy, and the environmental impact of oil extraction, are discussed. Additionally, social factors—such as labor conditions, energy security, and the demand for oil resources in developing countries—are explored in terms of their influence on market prices and policies. The article aims to identify how these factors have contributed to changes in the global oil market, particularly concerning price stability and market trends.